Influence of Age and Genetic Background on Ethanol Intake and Behavioral Response Following Ethanol Consumption and During Abstinence in a Model of Alcohol Abuse - Corongiu, Silvia; Dessì, Christian; Espa, Elena; Pisanu, Augusta; Pinna, Annalisa; Lecca, Daniele; Fenu, Sandro; Cadoni, Cristina (Frontiers in Behavioral Neuroscience, 2022)
Genetic background and age at first exposure have been identified as critical variables contributing to individual vulnerability to drug addiction. Evidence shows that genetic factors may account for 40-70 % of the variance in liability to addiction. Alcohol consumption by young people, especially in the form of binge-drinking, is becoming an alarming phenomenon predictive of future problems with drinking. Thus, the literature indicates the need to better understand the influence of age and genetic background on the development of alcohol dependence. To this aim, the inbred rat strains Lewis (LEW, addiction prone) and Fischer 344 (F344, addiction resistant) were used as a model of genetic vulnerability to addiction and compared with the outbred strain Sprague-Dawley (SD) in a two-bottle choice paradigm as a model of alcohol abuse. During a 9 week period, adolescent and adult male rats of the three strains were intermittently exposed to ethanol (20%) and water during three 24h sessions/week. Adult and adolescent SD and LEW rats escalated their alcohol intake over time reaching stable levels, while F344 rats did not escalated their intake, regardless of age at drinking onset. Among adolescents only F344 rats consumed a higher total amount of ethanol than adults, although only SD and LEW rats escalated their intake. Adult LEW rats, albeit having a lower ethanol consumption compared to SD rats, but greater than F344, showed a more compulsive intake, consuming higher amounts of ethanol during the first hour of exposure, reaching a higher degree of ethanol preference when start drinking as adolescents. Significant differences were observed between strains in behavioral activation following ethanol consumption and during withdrawal. The present results underscore the importance of individual genetic background and early onset of alcohol use in progression toward abuse and development of alcohol addiction.